1997
DOI: 10.1046/j.1365-313x.1997.12061399.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of environmental signals in flax. Their morphogenetic effect as enabled by a transient depletion of calcium

Abstract: It is possible to induce the formation of epidermal meristems in the hypocotyl of non‐injured and non‐hormone‐treated plantlets of flax, by combining various sorts of physical stimulations with a transient depletion of calcium. The characteristic times for the decrease of the tissue concentration of calcium during calcium depletion and for the recovery of the normal tissue concentration of calcium after resupplying the latter ion, are close to 1 day. The stimuli may correspond to wind or drought or even to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 0 publications
3
51
0
1
Order By: Relevance
“…Numerous experiments (data not shown) showed that, for plants subjected to a manipulation stimulus followed by calcium depletion, the I-value was usually in the range of 50 to 100 and sometimes much more, while the I-value for seedlings subjected to only the manipulation stimulus or to only the calcium depletion was usually in the range of 10 to 25 or even less. There is also a seasonal effect 8 and the I-values are particularly high, both for the stimulated seedlings and for the nonstimulated controls, when the experiments are carried out at the end of spring or beginning of summer. An example of a curve representing the mean number of meristems per seedling, n, as a function of the time, t (days), when the meristems were counted, and calculation of the integral, I, of this curve.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Numerous experiments (data not shown) showed that, for plants subjected to a manipulation stimulus followed by calcium depletion, the I-value was usually in the range of 50 to 100 and sometimes much more, while the I-value for seedlings subjected to only the manipulation stimulus or to only the calcium depletion was usually in the range of 10 to 25 or even less. There is also a seasonal effect 8 and the I-values are particularly high, both for the stimulated seedlings and for the nonstimulated controls, when the experiments are carried out at the end of spring or beginning of summer. An example of a curve representing the mean number of meristems per seedling, n, as a function of the time, t (days), when the meristems were counted, and calculation of the integral, I, of this curve.…”
Section: Resultsmentioning
confidence: 98%
“…[4][5][6][7][8][9][10][11][12] The response of plants to stimuli involves changes in the level of free calcium in the cytosol and such changes exhibit complex spatio-temporal dynamics. [13][14][15][16][17][18][19][20] Using the model of the induction of epidermal meristems in the hypocotyl of flax seedlings, [7][8][9][10][11] our group has shown that when flax seedlings (a few days in age) were subjected to both an abiotic stimulus and a 1 to 3 day-long depletion of calcium in the nutrient medium, they developed numerous meristems over the following fortnight. [7][8] These abiotic stimuli included a manipulation stimulus, wind, drought stress, cold shock, and low intensity electromagnetic radiation over a wide range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Abiotic stimuli such as the manipulation of flax seedlings followed at a later time by a temporary depletion (e.g., for one day) of calcium in the nutrient medium leads to a production of epidermal meristems in the hypocotyl; without either the abiotic stimulus or the calcium depletion, the meristem production does not occur. 23 The degree of leaf-folding of Mimosa (see above) is less in strong light possibly because the greater risk of predation is outweighed by the benefit of increased photosynthesis 20 but also perhaps because, in the theater management model, light intensity is central to the circadian and other rhythms needed for the interpretation of information.…”
Section: Examples Of the Sequential Aspect Of Plant Memorymentioning
confidence: 99%
“…; cela a donné lieu à une énorme quantité de données expérimentales ; la question a été abordée sous un nouvel angle par la référence à une succession signal -récep-tion du signal -transformation du signal en message -transmission du message -réception et traduction du message -réponse de l'effecteur (Champagnat & Desbiez, 1994) ; cet enchaînement peut comporter des mécanismes très variés, avec, au moins dans certains cas, une onde de dépolarisation comme support de la transmission du message ou (et) une onde de pression hydraulique (Malone, 1996) et parfois des phénomènes de mise en mémoire de l'information (voir Thellier et al, 1982 ;Desbiez et al, 1991Desbiez et al, , 1992Desbiez et al, , 1994Verdus et al, 1997), sans oublier le rôle des gènes eux-mêmes.…”
Section: B Les Messagesunclassified